Psychological Effects of Skin Incision Size in Minimally Invasive Valve Surgery Patients. Issue 6 (November 2020) - Piarulli, Alessandra; Chiariello, Giovanni Alfonso; Bruno, Piergiorgio; Cammertoni, Federico; Rabini, Alessia; Pavone, Natalia; Pasquini, Annalisa; Ferraro, Francesco; Mazza, Andrea; Nesta, Marialisa; Iafrancesco, Mauro; Colizzi, Christian; et al.
Objective: Clinical benefits of minimally invasive cardiac valve surgery (MIVS) have been reported. Improved postoperative mental status was never analyzed with dedicated psychological tests. In the present study we intend to investigate potential benefits of MIVS for patient psychological well-being, with special attention to the relevance of the patient perception of the chest surgical scar, of the self body image and cosmetic aspects. Methods: Between 2016 and 2017, 87 eligible patients, age 66.5 ± 14.5 years, operated on for heart valve surgery, underwent either conventional full sternotomy (CS; n = 48) or MIVS by V-shape hemi-sternotomy approach ( n = 39). Before selection of the surgical approach, patients had undergone preoperative evaluation of their psychological status using Beck Depression Inventory-II (BDI-II), State-Trait Anxiety Inventory Form Y (STAI-Y), and EuroQol-5D (EQ-5D) psychological tests. Six months postoperatively, patients filled in dedicated questionnaires to assess their psychological status, quality of life, and subjective perception, thus repeating the above-mentioned tests and adding the Body Image Questionnaire (BIQ) and Patient and Observer Scar Assessment Scale (POSAS) v2.0 tests for scar-healing process evaluation. Results: No patient died during the study.The 4 post-test scales of psychological well-being (BDI-II P = 0.04, STAI-Y P = 0.04, 2 indices of EQ-5D P = 0.03, P = 0.01) showed significant differences between the MIVS group and CS group, with MIVS-small incision patients having lower level of depression and anxiety symptoms and better quality of life. Mean score differences of scar perception (BIQ and POSAS v2.0) were significant, with MIVS patients having evaluated the scar quality significantly better than CS patients. Conclusions: MIVS appears associated with significant esthetical and related psychological benefits, as documented by technical tests. These findings should be considered when selecting the most appropriate technique for heart valve surgery.